Contamination of domestic groundwater systems by verotoxigenic escherichia coli (VTEC), 2003–2019: A global scoping review. (1st January 2021) - Chique, C.; Hynds, P.; Burke, L.P.; Morris, D.; Ryan, M.P.; O'Dwyer, J.
Highlights: Global review of VTEC prevalence in 'domestic' groundwater sources. VTEC can occur in groundwater sources and is a public health concern. Critical lack of understanding of VTEC transport into groundwater sources evident. Highly applicable VTEC to 'generic' E. coli ratios estimated. Abstract: Verocytotoxin-producing E. coli (VTEC) are important agents of diarrhoeal disease in humans globally. As a noted waterborne disease, emphasis has been given to the study VTEC in surface waters, readily susceptible to microbial contamination. Conversely, the status of VTEC in potable groundwater sources, generally regarded as a "safe" drinking-water supply remains largely understudied. As such, this investigation presents the first scoping review seeking to determine the global prevalence of VTEC in groundwater supply sources intended for human consumption. Twenty-three peer-reviewed studies were identified and included for data extraction. Groundwater sample and supply detection rates (estimated 0.6 and 1.3%, respectively) indicate VTEC is infrequently present in domestic groundwater sources. However, where generic (fecal indicator) E. coli are present, the VTEC to E. coli ratio was found to be 9.9%, representing a latent health concern for groundwater consumers. Geographically, extracted data indicates higher VTEC detection rates in urban (5.4%) and peri‑urban (4.9%) environments than in rural areas (0.9%); however, this finding is confounded by the predominance of research studies in lower income regions. Climate trends indicate local environments classified as 'temperate' (14/554; 2.5%) and 'cold' (8/392; 2%) accounted for a majority of supply sources with VTEC present, with similar detection rates encountered among supplies sampled during periods typically characterized by 'high' precipitation (15/649; 2.3%). Proposed prevalence figures may find application in preventive risk-based catchment and groundwater quality management including development of Quantitative Microbial Risk Assessments (QMRA). Notwithstanding, to an extent, a large geographical disparity in available investigations, lack of standardized reporting, and bias in source selection, restrict the transferability of research findings. Overall, the mechanisms responsible for VTEC transport and ingress into groundwater supplies remain ambiguous, representing a critical knowledge gap, and denoting a distinctive lack of integration between hydrogeological and public health research. Key recommendations and guidelines are provided for prospective studies directed at increasingly integrative and multi-disciplinary research. Graphical abstract: Image, graphical abstract